(untitled) (Revista de Estudios Europeos, 2026)
The Green Deal set out a new growth strategy for the European Union. The strategy was based on the efficient use of resources with no greenhouse gas emissions. The implementation of the Green Deal required an investment plan. The Plan aims to adapt production processes towards the use of non polutting energies. For this reason, the investments have been incorporated into the Community budget with new economic resources. The analysis of the budget and revenue applicable to the Green Deal are relevant for the purposes of determining the growth strategy for European Union.